The relationship of medication adherence and lifestyle on the quality of life of type 2 diabetes mellitus patients at Harapan Bunda Hospital Batam - Sari, Yelly Oktavia; Nasif , Hansen; Yunaspi, Rakhmi Febrina (Institute of Computer Science (IOCS), 2024)
Diabetes mellitus is a leading endocrine disorder throughout the world. Diabetes mellitus requires appropriate management so that the quality of life of DM patients is well maintained so that patients can maintain a sense of comfort and health. Successful treatment can improve the patient's quality of life and prevent complications. The aim of this study was to assess the relationship between adherence to medication use and lifestyle in diabetes mellitus patients, using descriptive analytical research methods with a cross sectional design conducted at the outpatient installation of Harapan Bunda Hospital, Batam with a sample of 350 patients who were matched to predetermined criteria. Bivariate analysis used chi square and it was found that compliance with medication use and the quality of life of type 2 DM patients was p = 0.059 > α=0.05, while the relationship between lifestyle and quality of life of type 2 DM patients was p = 0.000 < α=0.05. The conclusion of the study is that there is no relationship between adherence to medication use, while lifestyle is related to the quality of life of type 2 DM patients.